2008
DOI: 10.1093/jac/dkm518
|View full text |Cite
|
Sign up to set email alerts
|

Activities of voriconazole, itraconazole and amphotericin B in vitro against 590 moulds from 323 patients in the voriconazole Phase III clinical studies

Abstract: Voriconazole shows activity, in vitro, similar to that of itraconazole against a wide range of moulds. It is also active against some isolates not susceptible to itraconazole or amphotericin B, but not the Zygomycetes. The relationship between voriconazole MIC and clinical outcome requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…Novel systems for detection of circulating fungal cell wall markers and/or DNA in blood and other body fl uids or in affecting tissues may improve the laboratory diagnosis of disseminated aspergillosis (15,23). Our results of in vitro resistance to amphotericin B and susceptibility to voriconazole were comparable with the published data on in vitro activities of these antifungal agents for 13 worldwide clinical A. nidulans isolates from different body sites including brain/CSF (24). Poor response and high failure rates have been reported in patients with A. nidulans cerebral infection who were treated with amphotericin B (21).…”
Section: Casesupporting
confidence: 82%
“…Novel systems for detection of circulating fungal cell wall markers and/or DNA in blood and other body fl uids or in affecting tissues may improve the laboratory diagnosis of disseminated aspergillosis (15,23). Our results of in vitro resistance to amphotericin B and susceptibility to voriconazole were comparable with the published data on in vitro activities of these antifungal agents for 13 worldwide clinical A. nidulans isolates from different body sites including brain/CSF (24). Poor response and high failure rates have been reported in patients with A. nidulans cerebral infection who were treated with amphotericin B (21).…”
Section: Casesupporting
confidence: 82%
“…; 32,33 furthermore, it possesses potent in vitro activity against a wide range of other molds. 12 Voriconazole is available in both oral and intravenous formulations, which allows continuation of therapy in patients who have difficulty in swallowing (due to © F e r r a t a S t o r t i F o u n d a t i o n severe mucositis, for example) and can, therefore, cover the entire risk period of invasive fungal infections in HSCT patients, unlike other azoles that are only available as oral formulations. The availability of oral voriconazole makes the agent convenient for outpatient use, for example, in patients recovering from neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…10 Voriconazole is a broad-spectrum second-generation triazole, available in both oral and intravenous formulations, with potent activity against a wide variety of clinically significant molds and yeasts. 11,12 In a large, prospective, randomized trial, voriconazole was shown to provide a significant survival benefit, as well as superior efficacy and safety, over amphotericin B as first-line treatment of proven or probable invasive aspergillosis. 13 Furthermore, exploratory studies have shown that voriconazole is effective as secondary prophylaxis of invasive fungal infections in leukemia patients and HSCT recipients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Voriconazole (VRCZ), from a newer generation of triazoles, has also potent anti-aspergillus activity in vivo and in vitro. 18,19 Our study is the first prospective large-scale trial comparing intravenous MCFG and intravenous VRCZ as induction therapy in CPA patients who require immediate treatment.…”
Section: Introductionmentioning
confidence: 99%